Implementing Management Accounting Information Systems using Software Applications and its Implications on Individual Performance - Hertati*, Lesi; Asmawati, Asmawati; Syafitri, Lili; Ilyas, Meifida; Safkaur, Otniel (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
This study aims to determine the effect of accounting training applications, and accounting information system techniques on the implementation of management accounting information systems, and implications on the individual performance of retail organization managers. This study uses primary data with population units used by units related to retail store management employees, namely 10 retail stores in South Sumatra by using a probability sampling technique for as many as 155 retail store manager employees. The results of the study prove that the application of accounting training, and accounting information system techniques have an effect on the application of management accounting information systems resulting in the individual performance of information system software users. Keywords: Accounting Training Application; Accounting Information System Engineering; Application of Management Accounting Information System; Information System Software; Finance Penelitian ini bertujuan untuk mengetahui pengaruh aplikasi pelatihan akuntansi, teknik sistem informasi akuntansi terhadap penerapan sistem informasi akuntansi manajemen implikasi pada kinerja individual pengelola organisasi retail. Penelitian ini menggunakan data primer dengan unit populasi yang digunakan unit-unit terkait karyawan pengelola toko retail yaitu 10 toko-toko retail yang ada di Sumatera Selatan dengan menggunakan teknik probability sampling sebanyak 155 karyawan pengelola toko retail. Hasil penelitian membuktikan bahwa aplikasi pelatihan akuntansi, teknik sistem informasi akuntansi berpengaruh pada penerapan sistem informasi akuntansi manajemen berakibat pada kinerja individual pengguna software sistem informasi. Kata Kunci: Aplikasi Pelatihan Akuntasi; Teknik Sistem Informasi Akuntansi; Penerapan Sistem Informasi Akuntansi Manajemen; Software Sistem Informasi; Keuangan